Plato Expels the Poets from the Ideal Republic. (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Admission speech to the Chilean Academy of Language as a corresponding member, by Osorno, delivered on June 1, 2001, in the Lamp Room of the Cultural Center of the Illustrious Municipality of Osorno.